CCCs off-axial orientation sensitivity analysis in hole pin-bearing failure via hierarchical multiscale simulation framework. (15th April 2023) - Zhang, Yanfeng; Wu, Linzhi; Sun, Yuguo; Ma, Li; Pan, Shidong; Wang, Bing; Xiong, Jian; Zhou, Zhengong
Abstract: In current investigation, a sequential multiscale modelling strategy together with corresponding experimental validation aimed to evaluate the influence of off-axial orientation on three-dimensional orthogonal woven carbon/carbon composites (3DOWCCCs) pin-bearing failure behavior. A hierarchical numerical simulation methodology at micro−/ meso −/macroscales was developed to obtain the predictions. With the intention of acquiring precise mechanical responses of unnotched 3DOWCCCs, fiber and void stochastic arrangements in micro-level representative volume elements (RVEs) were generated using Random Sequential Adsorption (RSA) algorithm, meanwhile the geometrical reconstruction of meso-level RVE was accomplished via X-ray computed tomography (X-CT). Moreover, off-axial angle sensitivity analysis was presented through the comparison between macroscale modelling and testing results. The stress interaction and coupling impacts were embedded in material constitutive laws, which combined Murakami-Ohno theory for yarn based on continuum damage mechanics, and exponential damage rule for carbon matrix, incorporating trilinear cohesive zone model (CZM) for interface, and the achieved predictions agreed reasonably well with the experimental results. It is concluded that, for on-axial specimen, the warp yarns fracture and material out-of-plane swelling were the primary damage mechanism, while the material out-of-plane swelling in conjunction with yarns in-plane rotation dominated the structural failure under off-axial cases.